Formação do complexo de inclusão entre linalol e ciclodextrinas - Bonetti, Priscila (2009)
The objective of this work was to study the complexation of linalool fragrance in cyclodextrins. The used fragrance was linalool, a substance applied as a fixer perfumes, that has high volatility and is weakly dissolvable in water. The natural cyclodextrins used in this work was,α- ,ß and-y cyclodextrin, and the modified cyclodextrin hydroxypropyl-ß cyclodextrin. After study the theorist viability of the cyclodextrins capacity to form inclusion complexes with linalool, was observed that only the-CD doesnt have capacity to include linalool in its cavity. The stability constants, that was determined using the phase-solubility diagram, were 281,96 M-1; 423,61 M-1 e 286,97 M-1, to the systems linalool-CD, linalool/-yCD and linalool/HP,ß CD, respectively. The phase-solubility diagrams also showed that the substract´s solubility presents a linear increase with the CD concentration´s increase, suggesting formation of a 1:1 complex (linalool:CD), to all the systems. The complexation efficiency showed that to the-,ßCD one in each four molecules of -,ß CD in solution form dissolvable complex in water with linalool. The HP,ß-CD showed bigger probability of complexation than-CD (1 in each 3 molecules). The-CD showed the biggest probability to form inclusion complexes with the fragrance (57%), that is, 1 in each 2 or 3 molecules form complexes. viii The inclusion complexes were prepared by co-precipitation method, in molar rates 1:1 and 1:2 (linalool:CD), and characterized by Fourier Transform Infrared Spectroscopy (FT-IR), Nuclear Magnetic Resonance (RMN-H1), Differential ,Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and Derivative Thermogravimetric Analisis (DTA). These thecniques confirmed the inclusion complex formation between linalool and cyclodextrins. The thermal decomposition analysis permitted to presume that the process of decomposition of the-CD-CD, HP-CD and their respective complexes are simple first-order reactions. It was concluded also that, comparing the inclusion complexes prepared with-CD, the activation energy of the supposed complex in molar rate of 1:1 is bigger than the activation energy of the complex in molar rate of 1:2; the results for the inclusion complexes prepared with HP-CD showed the inverse. Even though the-CD showed better complexation efficiency with linalool, compared with the others CDs, the inclusion complex prepared with-CD showed better results in the characterization of the products by FT-IR, DSC, TGA e DTG; besides, from the economic point of view,-CD has the advantage of the others, because it is the cyclodextrin with smaller price in the market